A Perspective of New Critical Approaches: A critical Review on the Book “Minhaj Al-Naghd Al-Moaser” - Azade Montazeri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Along with the growth and advancement of human sciences and knowledge in the Western countries and their followers, new critical approaches have manifested in Arabic culture by various cultural exchanges, and it encourages Arabic critics to take advantage of the latest global critical results. Western criticism has always been gravitated by many adherents who completely ignore their original legacy, but some such as Salah Fazl, an Egyptian well-known researcher and critic, has tried to introduce the results of critical studies and to apply them in all parts of Arabic communities using intellectual and reasonable attitude, and he has scrutinized the old and new Arabic criticism efforts very carefully. In this regard, this paper has explored and studied the book “Minhaj Al-Naghd Al-Moaser” written by Salah Fazl using quantitative and qualitative approaches, and it has evaluated the strengths and weaknesses of the content and form of the mentioned work as well. The results of this study have revealed that the mentioned book has not been written in an academic way due to the lack of references and citations, but it has been written in a way that the author calls it “Oral writing”, and the author of this book is influenced by the writing method used by Taha Hossein and Mohammad Mandoor. Therefore, the author has made impressive strides towards the simple andaccurate understanding of the critical content of this book by its addresses.